Estimate of Changes in Carbon Stocks Based on Land Cover Changes in the Leuser Ecosystem Area (LEA) Indonesia - Hermon, Dedi (Forum Geografi, 2015)
This research aimed at designing the model of land cover changes in 1990 and 2014, and estimating carbon stock changes in each land cover in Leuser Ecosystem Area (LEA). The spatial model of land cover changes was analyzed by interpreting Landsat 5 TM imagery in 1990 and Landsat 7 ETM+ imagery in 2014 with ERDAS 9.1 and Land Change Modeller (LCM) in Idrisi TerrSet v.18. The analysis of land area changes (ha) in each land cover from 1990 to 2014 used ERDAS 9.1 with tools Interpreter (GIS Analysis-Matrix). Systematic survey method was employed in order to analyze carbon stocks. The sampling technique was stratified purposive composite sampling which used plot technique. The estimate of tree biomass used allometric equation. The estimate of carbon stocks in each land cover in 1990 was measured based on the total of carbon stocks in 2014 which was conversed with the areas of each land cover in 1990. Spatial model of land cover changes in LEA in 1990-2014 showed the changes of area in each land cover which caused the changes of carbon stocks in each land cover as well.